Mengatasi Toxic Masculinity Melalui Qirā’ah Mubādalah: Reinterpretasi Qiwāmah Dalam Surah An-Nisa Ayat 34 - Maulidina, Fitrotul; Mubarok, Mohammad Anas (Journal Of Gender, Child And Humanity Studies, 2025)
This study examines the use of Qirā’ah Mubādalah in understanding Surah An-Nisa’ verse 34 as an approach to addressing the issue of toxic masculinity. Through the Mubādalah perspective, which emphasizes reciprocity in the relationship between men and women, the study also refers to a supporting verse, An-Nisa’ verse 28, which indicates that men, like women, possess human traits that can involve weaknesses and limitations. This research highlights the concept of mutuality in gender relations and the importance of interpretive approaches that promote justice and equality. The research employs a qualitative approach with thematic interpretation (tafsir maudhu'i), analyzing primary sources from the Qur’an, classical and contemporary tafsir works, academic journals on gender, and masculinity references. The findings reveal that Qirā’ah Mubādalah offers a new paradigm for understanding qiwāmah as a shared and flexible responsibility, rather than absolute dominance. This approach is effective in deconstructing gender hierarchies, reducing the pressures of toxic masculinity, and building an egalitarian and cooperative family model. The study’s contribution lies in developing a progressive interpretation of the concept of qiwāmah that fosters substantive justice. However, its limitations include a focus on textual analysis and the need for further studies to examine practical implementation.